'Scum Cuddlers': police offender managers and the sex offenders' register in England and Wales. (18th May 2016) - Nash, Michael Robert
Abstract : Police services in England and Wales have been given an increasingly important role in community offender management. In many ways removed from what might traditionally and perhaps stereotypically be regarded as 'real' police work, it has nonetheless become a standard way of working for large numbers of police officers. One aspect of this work has brought the police into much closer and lasting professional contact with sex offenders as a result of new responsibilities given them under the Sex Offenders Act, 1997. This article discusses the findings of a small study of police offender managers (OMs) whose primary responsibility is to monitor and visit registered sex offenders in their homes. The findings give a snap shot of opinion from an offender management team, offering views on their role and the skills they perceive as necessary to assess and manage risks posed by sex offenders. It will also give the views of these OMs on the position they perceive their work to hold within the wider police community.